(untitled) (Research, Society and Development, 2019)
The objective of this work is to discuss the characteristics of the questionnaire as a tool for research, addressing the contexts of application, the aspects to be observed in the construction and some care in the use. The application of questionnaires as a data collection instrument is widely used in research in several areas of knowledge and can be adapted to different objectives and research formats. In this work a review about the elaboration and the use of questionnaires for researches and evaluation was carried out, resulting in the systematization of some notes and orientations their construction. Among the systematized aspects, it is important to carry out a previous careful research in order to recognize concepts to be approached and tests already validated on the proposed theme, the perception that the context in which the collection is performed needs to be considered in the research, the importance of choosing an instrument that effectively responds to the research objectives. Finally, it is emphasized that the questionnaire is a technical procedure that requires care regarding its elaboration, ordering, sequence, and ethical aspects involved, aiming the balance and the quality in the construction of the instrument to obtain results that meet the defined objectives.